Spatial synchrony in sub-arctic geometrid moth outbreaks reflects dispersal in larval and adult life cycle stages - Vindstad, Ole Petter Laksforsmo; Jepsen, Jane Uhd; Yoccoz, Nigel Gilles; Bjørnstad, Ottar Nordal; Mesquita, Michel d. S.; Ims, Rolf Anker (Journal of Animal Ecology, 2019)
This is the peer reviewed version of the following article: Vindstad, O.P.L., Jepsen, J.U., Yoccoz, N.G., Bjørnstad, O.N., Mesquita, M.d.S. & Ims, R.A. (2019). Spatial synchrony in sub-arctic geometrid moth outbreaks reflects dispersal in larval and adult life cycle stages. Journal of Animal Ecology, 88 (8), 1134-1145, which has been published in final form at https://doi.org/10.1111/1365-2656.12959 . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions . Spatial synchrony in population dynamics can be caused by dispersal or spatially correlated variation in environmental factors like weather (Moran effect). Distinguishing between these mechanisms is challenging for natural populations, and the study of dispersal‐induced synchrony in particular has been dominated by theoretical modelling and laboratory experiments. The goal of the present study was to evaluate the evidence for dispersal as a cause of meso‐scale (distances of tens of kilometres) spatial synchrony in natural populations of the two cyclic geometrid moths Epirrita autumnata and Operophtera brumata in sub‐arctic mountain birch forest in northern Norway. To infer the role of dispersal in geometrid synchrony, we applied three complementary approaches, namely estimating the effect of design‐based dispersal barriers (open sea) on synchrony, comparing the strength of synchrony between E. autumnata (winged adults) and the less dispersive O. brumata (wingless adult females), and relating the directionality (anisotropy) of synchrony to the predominant wind directions during spring, when geometrid larvae engage in windborne dispersal (ballooning). The estimated effect of dispersal barriers on synchrony was almost three times stronger for the less dispersive O. brumata than E. autumnata . Inter‐site synchrony was also weakest for O. brumata at all spatial lags. Both observations argue for adult dispersal as an important synchronizing mechanism at the spatial scales ...